A study on menstrual hygiene practices and problems amongst adolescent girls in Udaipur, Rajasthan, 2018 - Tundia, Mohnish N.; Thakrar, Dhara V. (International Journal Of Community Medicine And Public Health, 2018)
Background: Adolescence in girls has been recognized as a special period in life cycle. This period is marked with onset of menarche. It is linked with several perceptions and practices, which sometimes results in adverse health outcomes. So, this study was carried out to assess practices of menstruation in adolescent girls, to find out its related problems and socio-cultural beliefs. Methods: A cross sectional study was carried out during January-February 2018 in two schools of Udaipur using convenient sampling method with 440 sample size. Participants were adolescent girls of 9 to 12 standard. Girls were asked to fill a pre formed, pre tested semi-structured questionnaire. Results: Here 68.41% girls gave history of abdominal pain as premenstrual symptoms (PMS). School absenteeism was found 44.54% due to menstruation related problems. Sanitary Napkins were used by 50.22% girls. And 66.54% girls were using water to clean genitals during menstruation. Restriction from attending religious functions was high (91.59%). Associations of absorbents used by participants with absorbents used by their mothers and sisters were statistically significant. Conclusions: Abdominal pain was main PMS. Restrictions due to menstruation were very highly imposed. There were all chances that same types of the adsorbent were used by the adolescent girls, which were used by their mothers and sisters.